Blueprint: Quurv Sdn Bhd “Dent Bottle Puller” / Mohd Faiz Fikri Mohammad Johar … [et al.] - Mohammad Johar, Mohd Faiz Fikri; Akmar, Nursyafika Syazani; Abdul Haris, Nurul Natasha; Abd Wahap, Umi Nadrah (2021)
QUURV Sdn. Bhd. is a supplier company which distributes a very handful, useful and affordable product. It produces a dent bottle puller to easy handling the dented bottle either in home or factory. This company is a startup private company that starts its operation in Penang and has been opened up to public on 2021. It is equally owned and managed by its four partners. It consists of Sales and Marketing Manager, Administrative Manager, Financial Manager and Operations Manager.